How do prosocial motivation and performance‐related pay interact in the workplace context? Evidence from the non‐profit sector. (15th March 2022) - Lanfranchi, Joseph; Narcy, Mathieu
Abstract: The aim of this paper is to analyse the effectiveness of performance‐related pay among employees that place high value on working in a job with a prosocial mission. More particularly, using a sample of 2, 648 employees coming from an original European dataset in 2004, we compare their subjective assessment of effectiveness of actual and hypothetical performance‐related pay on the work effort in the non‐profit and for‐profit sectors. Estimations of ordered probit models reveal that non‐profit employees consider the use and extension of performance‐related pay schemes to be less effective in terms of their level of effort than their for‐profit counterparts. In addition, this relative inefficiency in the non‐profit sector increases as the employee's intrinsic motivation becomes higher. Indeed, while in the non‐profit sector, a higher intrinsic motivation is associated with a lower stated impact of actual and hypothetical performance‐related pay on effort, intrinsic motivation and monetary incentives appear to be independent within the for‐profit sector. In conclusion, these results suggest that within pro‐social jobs the employee's intrinsic motivation is less compatible with the use of monetary incentives. Consequently, the principals of a non‐profit organization should make more extensive use of low‐powered monetary incentives than their for‐profit counterparts.